HUBUNGAN RESPONSE TIME PERAWAT DENGAN KESELAMATAN PASIEN DI RUANG INSTALASI GAWAT DARURAT (IGD) - Siregar, Ismuntania; Hamalding, Hermawati; Kartika; Idris, Syamsul; Batubara, Khairunnisa; Naiya, Sarah (Jurnal Keperawatan Dan Kesehatan Holistik, 2025)
Response time is wrong one method for prevent incident safety patient with speed and accuracy service patients arriving at the ER require standard with competence And his ability, so that can confirmed time quick response​ And service emergency with proper handling. Purpose​ study to determine the relationship between nurse response time and patient safety in the Emergency Room of the Regional Public Hospital. Tgk Chik Ditiro. Method study This use method Quantitative analytic with approach cross sectional. Population in study This is nurses who work in the Emergency Room of the Regional Public Hospital. Mr. Chik Ditiro as many as 54 nurses. Technique taking sample in study This is technique purposive sampling totaling 35 nurses as respondents. Results study show that majority of nurses response time is at on category fast as many as 23 respondents (65.7%), safety patient majority is at on category currently as many as 15 respondents (42.9%), and There is connection response time nurse with safety patient in the room Installation Emergency Emergency Hospital Tgk Chick Imitated with P-Value value 0.009 <0.05. Conclusion in study This that is: the relationship between nurse response time and patient safety in the Emergency Room of Tgk Chik Ditiro Hospital. Expected nurses should carry out training about response time so that more fast responsive in handle patient.